An Assessment of the Professional Development Needs of Foreign Language Teachers Who Teach Special Education Students - Batista-Arias, Waleska Y (ProQuest Dissertations & Theses, 2011)
Preservice training and district professional development (PD) programs have not prepared foreign language teachers to work with special education (SPED) students. Without such training, teachers may not be able to provide effective instruction to SPED students, and SPED students may not learn the subject matter. The research question for this study addressed how the district could provide teachers with differentiated learning opportunities for teaching SPED students. A PD plan was developed using differentiated instruction and constructivism as the theoretical basis. A concurrent triangulation mixed methods approach that included administering the Standards Assessment Inventory (SAI) survey, conducting interviews, and reviewing archived data was used. Eleven teachers participated in the study. A purposeful sample of 4 teachers was selected for interviews. Quantitative data were analyzed using descriptive statistics. Qualitative data were analyzed by memoing, coding, and identifying emerging themes. Data were integrated during the analysis phase to cross-validate qualitative findings. Through the study, it was identified that, although the district provided ongoing, job-embedded PD using varied PD delivery formats, these opportunities did not address SPED teaching strategies. It was, therefore, important to address this need through the PD plan. This study can contribute to positive social change by encouraging implementation of PD plans that provide foreign language teachers with the training necessary to acquire and implement SPED instructional strategies, which may result in greater access to foreign language study for SPED students at the middle school level.